Post-viral fatigue and COVID-19: lessons from past epidemics. Issue 2 (2nd April 2020) - Islam, Mohammed F.; Cotler, Joseph; Jason, Leonard A.
ABSTRACT: The COVID-19 pandemic, resulting from Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has severely impacted the population worldwide with a great mortality rate. The current article reviews the literature on short- and long-term health consequences of prior epidemics and infections to assess potential health complications that may be associated with post-COVID-19 recovery. Past research on post-epidemic and post-infection recovery has suggested that such complications include the development of severe fatigue. Certain factors, such as the severity of infection, in addition to the 'cytokine storm' experienced by many COVID-19 patients, may contribute to the development of later health problems. We suggest that the patterns observed in past epidemics and infections may re-occur in the current COVID-19 pandemic.